Polyoxymethylene composite and method for producing the same

CN122978642APending Publication Date: 2026-10-27CHINA ENERGY GRP NINGXIA COAL IND CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610885347.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]本发明的目的是为了克服现有技术存在的聚甲醛产品的耐候性较差,即抗紫外线功能较弱,同时由于助剂添加量很大,严重影响了聚甲醛产品的力学性能的问题,提供一种聚甲醛复合材料及其制备方法,该聚甲醛复合材料平衡和提高了聚甲醛产品的耐候、耐低温性能,并且由于助剂添加量较小,故对力学性能基本无不良影响,甚至还提高了产品的韧性,使之更适合应用于户外制品等领域

Benefits of technology

[0018]通过上述技术方案,通过引入式(I)所示的三嗪系化合物和聚乙二醇改性聚甲醛,提高了聚甲醛的抗紫外线能力,提高了聚甲醛耐低温性能,进而提高了聚甲醛的韧性,从而得到耐候、耐低温的聚甲醛复合材料,使之更适合应用于户外制品等领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978642A_ABST
    Figure CN122978642A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of high polymer materials, and discloses a polyformaldehyde composite material and a preparation method thereof. The polyformaldehyde composite material contains polyformaldehyde powder, a triazine compound shown in formula (I) and polyethylene glycol, wherein R1, R2, R3 and R4 are each C1-C6 alkyl; and R5 is C6-C 12 alkyl. The polyformaldehyde composite material has excellent ultraviolet resistance, aging resistance and low-temperature resistance. Formula (I)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a polyoxymethylene composite material and its preparation method. Background Technology

[0002] Polyoxymethylene (POM) resin is a thermoplastic. Its regular molecular chain configuration allows for rapid crystallization during melt processing, giving it excellent mechanical properties. It is one of the engineering plastics whose mechanical properties are closest to those of metallic materials, and it can replace metals such as steel, copper, zinc, and aluminum in many fields. POM resin possesses advantages such as wear resistance, creep resistance, fatigue resistance, oil resistance, chemical resistance, self-lubrication, good electrical properties, and dimensional stability. It can be used for extended periods in a temperature range of -40 to 100°C and is widely used in industrial machinery, automobiles, electronics, agriculture, light industry, chemicals, building materials, water conservancy, agricultural and forestry irrigation, and daily consumer goods. With the expansion of POM applications, POM products place higher demands on POM raw materials. For example, POM is widely researched and applied in outdoor sprinkler and drip irrigation. The weather resistance and low-temperature resistance of general-purpose POM cannot meet the needs of these bulk products. Therefore, a weather-resistant and low-temperature-resistant POM composite material and its preparation method have become an urgent research need. Summary of the Invention

[0003] The purpose of this invention is to overcome the problems of poor weather resistance and weak UV resistance in existing polyoxymethylene (POM) products, as well as the serious impact on the mechanical properties of POM products due to the large amount of additives. This invention provides a POM composite material and its preparation method. This POM composite material balances and improves the weather resistance and low-temperature resistance of POM products. Furthermore, due to the small amount of additives, it has virtually no adverse effect on the mechanical properties and even improves the toughness of the product, making it more suitable for applications in outdoor products and other fields.

[0004] To achieve the above objectives, a first aspect of the present invention provides a polyoxymethylene composite material comprising polyoxymethylene powder, a triazine compound of formula (I), and polyethylene glycol. Formula (I) Among them, R1, R2, R3 and R4 are each C1-C6 alkyl groups; R5 is C6-C 10 Alkyl groups.

[0005] Preferably, in formula (I), R1, R2, R3 and R4 are each methyl, ethyl or propyl; R5 is heptyl or octyl.

[0006] Preferably, relative to 100 parts by weight of the polyoxymethylene powder, the content of the triazine compound is 0.1-0.6 parts by weight; and the content of the polyethylene glycol is 1-5 parts by weight.

[0007] Preferably, the weight-average molecular weight of the polyethylene glycol is 4000-6000.

[0008] Preferably, the polyoxymethylene composite material further contains at least one of an antioxidant, a lubricant, an acid absorber, and an aldehyde absorber.

[0009] Preferably, the antioxidant content is 0.5-1 parts by weight relative to 100 parts by weight of the polyoxymethylene powder.

[0010] Preferably, the antioxidant is at least one of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate] and 2,2-bis[[3[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropoxy]methyl]-1,3-propadiyl-3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionate].

[0011] Preferably, the lubricant content is 0.5-1 parts by weight relative to 100 parts by weight of the polyoxymethylene powder.

[0012] Preferably, the lubricant is at least one of zinc stearate and N,N'-ethylenebisstearamide.

[0013] Preferably, the content of the acid absorbent is 0.5-1 parts by weight relative to 100 parts by weight of the polyoxymethylene powder.

[0014] Preferably, the acid absorbent is at least one of calcium carbonate and calcium oxide.

[0015] Preferably, the content of the formaldehyde absorbent is 0.5-1 parts by weight relative to 100 parts by weight of the polyoxymethylene powder.

[0016] Preferably, the formaldehyde absorbent is at least one of melamine, dicyandiamide, and copolyamide.

[0017] A second aspect of the present invention provides a method for preparing the above-mentioned polyoxymethylene composite material, the method comprising the following steps: (1) Feed polyoxymethylene powder into the main feed hopper of the twin-screw extruder; (2) Add polyethylene glycol into the first additive chamber of the twin-screw extruder; (3) Mix the triazine compound shown in formula (I), an optional antioxidant, an optional lubricant, an optional acid absorber and an optional aldehyde absorber, and put the resulting mixture into the second auxiliary agent compartment; (4) The processing temperature of the twin-screw extruder is set at 200℃, and the mixture is melt-blended and extruded to obtain polyoxymethylene composite material.

[0018] By introducing the triazine compound shown in formula (I) and polyethylene glycol to modify polyoxymethylene, the UV resistance of polyoxymethylene is improved, the low temperature resistance of polyoxymethylene is improved, and the toughness of polyoxymethylene is improved, thus obtaining a weather-resistant and low-temperature resistant polyoxymethylene composite material, making it more suitable for application in outdoor products and other fields. Detailed Implementation

[0019] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0020] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0021] The polyoxymethylene composite material of the present invention contains polyoxymethylene powder, a triazine compound of formula (I), and polyethylene glycol. Formula (I) Among them, R1, R2, R3, and R4 are each C1-C6 alkyl groups; R5 is a C6-C6 alkyl group. 10 Alkyl groups.

[0022] The polyoxymethylene composite material according to the present invention has excellent UV resistance, aging resistance, and low temperature resistance, and is suitable for the manufacture of sprinkler and drip irrigation equipment with high requirements for impact resistance, outdoor weather resistance, and low temperature resistance.

[0023] In the polyoxymethylene composite material of the present invention, in order to improve the UV oxidation resistance of polyoxymethylene, in formula (I), R1, R2, R3 and R4 are each preferably methyl, ethyl or propyl, more preferably methyl; R5 is preferably heptyl or octyl, more preferably octyl.

[0024] In the polyoxymethylene composite material of the present invention, in order to improve the UV resistance, low temperature resistance and toughness of formaldehyde, the content of the triazine compound is preferably 0.1-0.6 parts by weight, more preferably 0.2-0.6 parts by weight, relative to 100 parts by weight of the polyoxymethylene powder; the content of the polyethylene glycol is preferably 1-5 parts by weight, more preferably 2-5 parts by weight.

[0025] In the polyoxymethylene composite material of the present invention, the weight-average molecular weight of the polyethylene glycol can be 4000-6000, preferably 5000-6000.

[0026] In the polyoxymethylene composite material of the present invention, in order to improve the antioxidant and decomposition resistance of polyoxymethylene, the polyoxymethylene composite material preferably contains at least one of antioxidant, lubricant, acid absorber and aldehyde absorber.

[0027] In the polyoxymethylene composite material of the present invention, the content of the antioxidant relative to 100 parts by weight of the polyoxymethylene powder can be 0.5-1 parts by weight, preferably 0.75-1 parts by weight. The antioxidant can be at least one of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate] and 2,2-bis[[3[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropoxy]methyl]-1,3-propadiyl-3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionate, preferably triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate].

[0028] In the polyoxymethylene composite material of the present invention, the content of the lubricant relative to 100 parts by weight of the polyoxymethylene powder can be 0.5-1 parts by weight, preferably 0.75-1 parts by weight. The lubricant can be at least one of zinc stearate and N,N'-ethylenebisstearamide, preferably zinc stearate.

[0029] In the polyoxymethylene composite material of the present invention, the content of the acid absorber relative to 100 parts by weight of the polyoxymethylene powder can be 0.5-1 parts by weight, preferably 0.75-1 parts by weight. The acid absorber can be at least one of calcium carbonate and calcium oxide, preferably calcium carbonate.

[0030] In the polyoxymethylene composite material of the present invention, the content of the formaldehyde absorbent relative to 100 parts by weight of the polyoxymethylene powder can be 0.5-1 parts by weight, preferably 0.75-1 parts by weight. The formaldehyde absorbent can be at least one of melamine, dicyandiamide, and copolyamide (COPA), preferably melamine.

[0031] In some embodiments, the polyoxymethylene composite material of the present invention contains polyoxymethylene powder, a triazine compound of formula (I), polyethylene glycol, an antioxidant, a lubricant, an acid absorbent, and an aldehyde absorbent. Formula (I) Wherein, R1, R2, R3, and R4 are each C1-C6 alkyl groups; R5 is a C6-C10 alkyl group; the weight-average molecular weight of the polyethylene glycol is 4000-6000; relative to 100 parts by weight of the polyoxymethylene powder, the content of the triazine compound is 0.1-0.6 parts by weight, the content of the polyethylene glycol is 1-5 parts by weight, the content of the antioxidant is 0.5-1 parts by weight, the content of the lubricant is 0.5-1 parts by weight, the content of the acid scavenger is 0.5-1 parts by weight, and the content of the aldehyde scavenger is 0.5-1 parts by weight; the antioxidant... The lubricant is at least one of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate] and 2,2-bis[[3[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropoxy]methyl]-1,3-propadiyl-3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionate; the lubricant is at least one of zinc stearate and N,N'-ethylenebisstearamide; the acid absorber is at least one of calcium carbonate and calcium oxide; and the aldehyde absorber is at least one of melamine, dicyandiamide, and copolyamide.

[0032] In other embodiments, the polyoxymethylene composite material of the present invention comprises polyoxymethylene powder, a triazine compound of formula (I), polyethylene glycol, an antioxidant, a lubricant, an acid absorber, and an aldehyde absorber. Formula (I) Wherein, R1, R2, R3, and R4 are each ethyl or propyl; R5 is heptyl or octyl; the weight-average molecular weight of the polyethylene glycol is 4000-6000; relative to 100 parts by weight of the polyoxymethylene powder, the content of the triazine compound is 0.1-0.6 parts by weight, the content of the polyethylene glycol is 1-5 parts by weight, the content of the antioxidant is 0.5-1 parts by weight, the content of the lubricant is 0.5-1 parts by weight, the content of the acid absorber is 0.5-1 parts by weight, and the content of the aldehyde absorber is 0.5-1 parts by weight; the antioxidant is triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate]; the lubricant is zinc stearate; the acid absorber is calcium carbonate; and the aldehyde absorber is melamine.

[0033] In other embodiments, the polyoxymethylene composite material of the present invention comprises polyoxymethylene powder, a triazine compound of formula (I), polyethylene glycol, an antioxidant, a lubricant, an acid absorber, and an aldehyde absorber. Formula (I) Wherein, R1, R2, R3, and R4 are each methyl; R5 is octyl; the weight-average molecular weight of the polyethylene glycol is 4000-6000; relative to 100 parts by weight of the polyoxymethylene powder, the content of the triazine compound is 0.1-0.6 parts by weight, the content of the polyethylene glycol is 1-5 parts by weight, the content of the antioxidant is 0.5-1 parts by weight, the content of the lubricant is 0.5-1 parts by weight, the content of the acid absorber is 0.5-1 parts by weight, and the content of the aldehyde absorber is 0.5-1 parts by weight; the antioxidant is triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate]; the lubricant is zinc stearate; the acid absorber is calcium carbonate; and the aldehyde absorber is melamine.

[0034] The present invention also provides a method for preparing the above-mentioned polyoxymethylene composite material, the method comprising the following steps: (1) Feed polyoxymethylene powder into the main feed hopper of the twin-screw extruder; (2) Add polyethylene glycol into the first additive chamber of the twin-screw extruder; (3) Mix the triazine compound shown in formula (I), an optional antioxidant, an optional lubricant, an optional acid absorber and an optional aldehyde absorber, and put the resulting mixture into the second auxiliary agent compartment; (4) The processing temperature of the twin-screw extruder is set at 200℃, and the mixture is melt-blended and extruded to obtain polyoxymethylene composite material.

[0035] According to the method described in this invention, by introducing the triazine compound shown in formula (I) and polyethylene glycol to modify polyoxymethylene, the UV resistance of polyoxymethylene is improved, the low temperature resistance of polyoxymethylene is improved, and the toughness of polyoxymethylene is improved, and a one-time modification process is achieved.

[0036] In the method described in this invention, the prepared polyoxymethylene composite material is processed from powder, not from polyoxymethylene granules.

[0037] The following examples further illustrate the polyoxymethylene composite material and its preparation method according to the present invention. These examples are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures; however, the scope of protection of the present invention is not limited to the following examples.

[0038] Unless otherwise specified, the experimental methods used in the following examples are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following examples are commercially available. The polyoxymethylene used in the examples was purchased from Ningxia Coal Industry Co., Ltd., a subsidiary of China Energy Investment Corporation, and its grade is MC90.

[0039] The structural formulas of the triazine compounds used in the following examples and comparative examples are as follows: Equation (II), It was purchased from Jiangsu Danxia New Materials Co., Ltd., and the product name is 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl]-5-(octoxy)phenol.

[0040] Example 1 (1) Add 100 parts by weight of polyoxymethylene powder into the main feed hopper of the twin-screw extruder; (2) Five parts by weight of polyethylene glycol PEG-6000 (purchased from Jiangsu Haian Petrochemical Plant, brand name PEG-6000, weight average molecular weight 6000) were added to the first additive bin of the twin-screw extruder; (3) Mix 0.6 parts by weight of the triazine compound of formula (II), 1 part by weight of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1 part by weight of zinc stearate, 1 part by weight of calcium carbonate and 1 part by weight of melamine, and put the resulting mixture into the second auxiliary agent compartment; (4) The processing temperature of the twin-screw extruder is set at 200℃, and the mixture is melt-blended and extruded to obtain polyoxymethylene composite material.

[0041] Example 2 (1) Add 100 parts by weight of polyoxymethylene powder into the main feed hopper of the twin-screw extruder; (2) One part by weight of polyethylene glycol PEG-6000 (purchased from Jiangsu Haian Petrochemical Plant, brand name PEG-6000, weight average molecular weight of 6000) was added to the first additive bin of the twin-screw extruder; (3) Mix 0.1 parts by weight of the triazine compound of formula (II), 0.5 parts by weight of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 0.5 parts by weight of zinc stearate, 0.5 parts by weight of calcium carbonate and 0.5 parts by weight of melamine, and put the resulting mixture into the second auxiliary agent compartment; (4) The processing temperature of the twin-screw extruder is set at 200℃, and the mixture is melt-blended and extruded to obtain polyoxymethylene composite material.

[0042] Example 3 (1) Add 100 parts by weight of polyoxymethylene powder into the main feed hopper of the twin-screw extruder; (2) Three parts by weight of polyethylene glycol PEG-4000 (purchased from Jiangsu Haian Petrochemical Plant, brand name PEG-6000, weight average molecular weight of 4000) were added to the first additive bin of the twin-screw extruder; (3) Mix 0.35 parts by weight of the triazine compound of formula (II), 0.75 parts by weight of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 0.75 parts by weight of zinc stearate, 0.75 parts by weight of calcium carbonate and 0.75 parts by weight of melamine, and put the resulting mixture into the second auxiliary agent compartment; (4) The processing temperature of the twin-screw extruder is set at 200℃, and the mixture is melt-blended and extruded to obtain polyoxymethylene composite material.

[0043] Example 4 Polyoxymethylene composite material was prepared according to the method of Example 1, except that 5 parts by weight of polyethylene glycol PEG-6000 were replaced with 7 parts by weight of polyethylene glycol PEG-6000.

[0044] Example 5 The polyoxymethylene composite material was prepared according to the method of Example 1, except that 0.6 parts by weight of the triazine compound of formula (II) was replaced with 1.5 parts by weight of the triazine compound of formula (II).

[0045] Example 6 Polyoxymethylene composite material was prepared according to the method of Example 1, except that 1 part by weight of zinc stearate was replaced with 2 parts by weight of zinc stearate.

[0046] Example 7 Polyoxymethylene composite material was prepared according to the method of Example 1, except that 1 part by weight of calcium carbonate was replaced with 2 parts by weight of calcium carbonate.

[0047] Example 8 The polyoxymethylene composite material was prepared according to the method of Example 1, except that 1 part by weight of melamine was replaced with 2 parts by weight of melamine.

[0048] Example 9 Polyoxymethylene composite material was prepared according to the method of Example 1, except that zinc stearate was not added.

[0049] Example 10 Polyoxymethylene composite material was prepared according to the method of Example 1, except that calcium carbonate was not added.

[0050] Example 11 Polyoxymethylene composite material was prepared according to the method in Example 1, except that melamine was not added.

[0051] Example 12 (1) Mix 100 parts by weight of polyoxymethylene powder, 5 parts by weight of polyethylene glycol PEG-6000 (purchased from Jiangsu Haian Petrochemical Plant, brand name PEG-6000, weight average molecular weight of 6000), 0.6 parts by weight of the triazine compound shown in formula (II), 1 part by weight of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 1 part by weight of zinc stearate, 1 part by weight of calcium carbonate and 1 part by weight of melamine, and feed them into the main feed bin of a twin-screw extruder; (2) The processing temperature of the twin-screw extruder is set at 200℃, and the mixture is melt-blended and extruded to obtain polyoxymethylene composite material.

[0052] Comparative Example 1 Polyoxymethylene composite material was prepared according to the method of Example 1, except that polyethylene glycol PEG-6000 was not added.

[0053] Comparative Example 2 Polyoxymethylene composite material was prepared according to the method in Example 2, except that polyethylene glycol PEG-6000 was not added.

[0054] Comparative Example 3 Polyoxymethylene composite material was prepared according to the method of Example 3, except that polyethylene glycol PEG-6000 was not added.

[0055] Comparative Example 4 The polyoxymethylene composite material was prepared according to the method of Example 1, except that the triazine compound shown in formula (II) was not added.

[0056] Comparative Example 5 The polyoxymethylene composite material was prepared according to the method of Example 2, except that the triazine compound shown in formula (II) was not added.

[0057] Comparative Example 6 The polyoxymethylene composite material was prepared according to the method of Example 3, except that the triazine compound shown in formula (II) was not added.

[0058] Comparative Example 7 Polyoxymethylene composite material was prepared according to the method of Example 1, except that the triazine compound shown in formula (II) was replaced with 2-hydroxy-4-dodecyloxybenzophenone.

[0059] Comparative Example 8 Polyoxymethylene composite material was prepared according to the method of Example 1, except that the triazine compound shown in formula (II) was replaced with benzophenone (BZP).

[0060] Comparative Example 9 Polyoxymethylene composite material was prepared according to the method of Example 1, except that the triazine compound shown in Formula (II) was replaced with benzotriazole (BZT).

[0061] Test case The polyoxymethylene composite materials prepared in Examples 1-12 and Comparative Examples 1-9 were processed under uniform injection molding conditions to produce standard test strips for tensile, flexural, and impact testing. The standard test strips were then subjected to mechanical property testing, and the test data are recorded in Table 1. Next, the standard test strips underwent ultraviolet (UV) aging experiments. After UV aging, each group of samples underwent a period of light exposure (UVA-340), followed by a cyclical test with a no-irradiation period. The samples were exposed to irradiation at 60°C for 12 hours, followed by a no-irradiation condensation exposure at 50°C for 12 hours. This experimental process was repeated cyclically for a total of 672 hours to ensure that the conditions during each exposure period reached equilibrium before further mechanical property testing. The test data are recorded in Table 2.

[0062] Table 1

[0063] As can be seen from the results in Table 1, before the UV aging test, the tensile, flexural, and impact properties of the polyoxymethylene composite materials prepared in Examples 1-12 were all better than those of the corresponding comparative groups. The main reason is that Examples 1-12 added triazine compounds, polyethylene glycol, antioxidants, lubricants, acid scavengers, and aldehyde scavengers as shown in Formula (I), while the comparative groups 1-3 did not add the toughening agent polyethylene glycol, so their toughness was slightly worse. The tensile, flexural, and impact properties of Examples 1-3 were basically equivalent to those of the comparative groups 4-6. The main reason is that the addition of 0.1-0.6 parts by weight of the triazine compounds shown in Formula (I) had little effect on the tensile, flexural, and impact properties of polyoxymethylene.

[0064] The toughness of Comparative Examples 4-6 was better than that of Comparative Examples 1-3, meaning they had better impact strength. This was mainly because Comparative Examples 4-6 added polyethylene glycol, while Comparative Examples 1-3 did not. PEG-6000, through its synergistic effect with triazine compounds, antioxidants, lubricants, acid scavengers, and aldehyde scavengers, improved the toughness of the material and reduced its brittleness, thereby improving the material's mechanical properties and durability.

[0065] Table 2

[0066] As shown in Table 2, after aging tests, the tensile, flexural, and impact properties of the polyoxymethylene composite materials prepared in Examples 1-12 were superior to those of the corresponding comparative examples. After UV aging tests, the tensile strength, fracture strain, flexural strength, and flexural modulus retention rates of the sample in Example 1 were approximately 90%, and the room temperature and low temperature impact strength retention rates were approximately 60%. After UV aging tests, the tensile strength, fracture strain, flexural strength, and flexural modulus retention rates of the sample in Example 2 were approximately 70% compared to before the UV aging test, and the room temperature and low temperature impact strength retention rates were approximately 40%. After UV aging tests, the tensile strength, fracture strain, flexural strength, and flexural modulus retention rates of the sample in Example 3 were approximately 80%, and the room temperature and low temperature impact strength retention rates were approximately 50%. This difference is mainly due to the different amounts of triazine compounds added as light stabilizers.

[0067] Comparative Examples 1-3 did not contain the toughening agent polyethylene glycol, but other additives were added as required. Therefore, their toughness was slightly worse than the corresponding samples in Examples 1-3, and their low-temperature resistance was not as good as that in Examples 1-3.

[0068] After UV aging tests, the tensile strength, fracture strain, flexural strength, and flexural modulus retention rates of samples 4-6 were approximately 50%, while the room temperature and low temperature impact strength retention rates were approximately 30%. The main reason is that samples 4-6 did not contain the triazine compound shown in formula (I), while other additives were added as required. Therefore, the weather resistance of samples 4-6 was extremely poor, resulting in a significant decrease in their tensile strength, flexural strength, room temperature and low temperature impact strength, and other mechanical properties due to UV exposure. Comparative samples 7-9 showed worse performance compared to Example 1, demonstrating that replacing the triazine compound with 2-hydroxy-4-dodecyloxybenzophenone, benzophenone (BZP), or benzotriazole (BZT) significantly reduced the performance of the polyoxymethylene product. This indicates that triazine compounds have a significant advantage in resisting UV aging, giving polyoxymethylene higher weather resistance.

[0069] In summary, the addition of the triazine compound shown in formula (I) improved the UV oxidation resistance of polyoxymethylene (POM); the addition of polyethylene glycol improved the toughness of POM, thereby enhancing its low-temperature resistance; and the addition of antioxidants, lubricants, acid scavengers, and aldehyde scavengers improved the antioxidant and decomposition resistance of POM. The weather resistance and low-temperature resistance of the samples in Examples 1-3 were higher than those of the comparative samples, with the sample in Example 1 exhibiting the best weather resistance and low-temperature resistance.

[0070] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A polyoxymethylene composite material, characterized in that, The polyoxymethylene composite material contains polyoxymethylene powder, a triazine compound of formula (I), and polyethylene glycol. Equation (I) Among them, R1, R2, R3 and R4 are each C1-C6 alkyl groups; R5 is C6-C 10 Alkyl groups.

2. The polyoxymethylene composite material according to claim 1, characterized in that, In formula (I), R1, R2, R3 and R4 are each methyl, ethyl or propyl; R5 is heptyl or octyl.

3. The polyoxymethylene composite material according to claim 1 or 2, characterized in that, The content of the triazine compound is 0.1-0.6 parts by weight relative to 100 parts by weight of the polyoxymethylene powder; the content of the polyethylene glycol is 1-5 parts by weight.

4. The polyoxymethylene composite material according to any one of claims 1-3, characterized in that, The weight-average molecular weight of the polyethylene glycol is 4000-6000.

5. The polyoxymethylene composite material according to any one of claims 1-4, characterized in that, The polyoxymethylene composite material also contains at least one of antioxidants, lubricants, acid absorbers, and aldehyde absorbers.

6. The polyoxymethylene composite material according to claim 5, characterized in that, The antioxidant content is 0.5-1 parts by weight relative to 100 parts by weight of the polyoxymethylene powder; Preferably, the antioxidant is at least one of triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate] and 2,2-bis[[3[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropoxy]methyl]-1,3-propadiyl-3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionate].

7. The polyoxymethylene composite material according to any one of claims 1-6, characterized in that, The content of the lubricant is 0.5-1 parts by weight relative to 100 parts by weight of the polyoxymethylene powder; Preferably, the lubricant is at least one of zinc stearate and N,N'-ethylenebisstearamide.

8. The polyoxymethylene composite material according to any one of claims 1-7, characterized in that, The content of the acid absorbent is 0.5-1 parts by weight relative to 100 parts by weight of the polyoxymethylene powder; Preferably, the acid absorbent is at least one of calcium carbonate and calcium oxide.

9. The polyoxymethylene composite material according to any one of claims 1-7, characterized in that, The content of the formaldehyde absorbent is 0.5-1 parts by weight relative to 100 parts by weight of the polyoxymethylene powder; Preferably, the formaldehyde absorbent is at least one of melamine, dicyandiamide, and copolyamide.

10. A method for preparing the polyoxymethylene composite material according to any one of claims 1-9, characterized in that, The method includes the following steps: (1) Feed polyoxymethylene powder into the main feed hopper of the twin-screw extruder; (2) Add polyethylene glycol into the first additive chamber of the twin-screw extruder; (3) Mix the triazine compound shown in formula (I), an optional antioxidant, an optional lubricant, an optional acid absorber and an optional aldehyde absorber, and put the resulting mixture into the second auxiliary agent compartment; (4) The processing temperature is set at 190-205℃ by a twin-screw extruder, and the mixture is melt-blended and extruded to obtain polyoxymethylene composite material.